Development and validation of the malay premature ejaculation diagnostic tool (MAPET): A two-phase study - Arasalingam, Shamini; Chong, Yew Siong; Sidi, Hatta; Ng, Chong Guan; Jaafar, Nik Ruzyanei Nik; Midin, Marhani; Das, Srijit; Alfonso, Cesar A. (International Islamic University Malaysia, 2018)
Introduction: A validated diagnostic questionnaire is needed in the South-East Asia region, particularly in Malaysia to detect Premature Ejaculation (PE). The objective of this study was to determine the linguistic validity of the Malay Premature Ejaculation Diagnostic Tool (MAPET). Materials and Methods: This study was conducted in a teaching hospital. The first phase involved experts' group discussions to develop the face, content, and factorial validity of the MAPET. The second phase measured the concurrent validity of MAPET. Results: We found that the MAPET has specificity, sensitivity, positive predictive value, and negative predictive value of 79.3%, 92%, 76.7% and 93.1%, respectively in the assessment of PE. The higher score indicates severity of PE. Conclusions: MAPET is a valid self-report instrument for the assessment of PE.